# Prove $\sum_{0}^{n}(-1)^i\binom{n}{i} = 0$ [closed]

I have to prove that $\sum_{0}^{n}(-1)^i\binom{n}{i} = 0$,

I know i have to use the binomial theorem,But i dont know how.

Thanks.

## closed as off-topic by Daniel W. Farlow, Claude Leibovici, user147263, colormegone, John BMar 16 '16 at 0:02

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Daniel W. Farlow, Claude Leibovici, John B
If this question can be reworded to fit the rules in the help center, please edit the question.

• Have you tried induction? – A. Prufrock Mar 15 '16 at 18:02
• I have to prove it with binomial theorem. – Noam Mar 15 '16 at 18:03
• Use the binomial theorem to expand $(1-1)^n$. – user296113 Mar 15 '16 at 18:03
• @user296113 What do you mean ? – Noam Mar 15 '16 at 18:03
• thanks, i solved it successfully using your help. – Noam Mar 15 '16 at 18:06

$$0 = \bigl((1+ (-1)\bigr)^n = \sum_{i=0}^n \binom ni 1^{n-i}(-1)^i = \sum_{i=0}^n \binom ni (-1)^i$$

The Binomial Theorem: $$(x+y)^n = \sum\limits_{i=0}^n \binom{n}{i}x^{n-i}y^i$$

For example $(x+y)^4 = x^4+4x^3y+6x^2y^2+4xy^3+y^4$

Using the above, notice what happens when $x=1$ and $y=-1$

$0=(1-1)=(1+(-1))^n=\sum\limits_{i=0}^n\binom{n}{i}1^{n-i}(-1)^i=\sum\limits_{i=0}^n\binom{n}{i}(-1)^i$

In general, with other sums like this, one can throw in additional factors of $1$ to an arbitrary power to notice the pattern.

For example, $\sum\limits_{i=0}^n\binom{n}{i} = \sum\limits_{i=0}^n\binom{n}{i}(1)^i(1)^{n-i} = (1+1)^n = 2^n$